O uso do jogo “física em movimento” como objeto de aprendizagem didático-integradora do ensino de física para as turmas de 1a série do ensino médio. - Rabelo, Jean Carlos Gomes (2021)
This dissertation aimed to provide an alternative way to combine knowledge with the practice of teaching Physics, as a way to increase the interest and receptivity of this subject, sometimes so criticized by students, as being, Physics, a monotonous and of little attractiveness and interest, due to the difficulty of their practical interaction. From a poll with EEEP high school students Juarez Távora, the need to add new teaching methodologies was verified, so that the student could, in addition to feeling more motivated, interact more with the discipline of Physics.As a result, the board game “PHYSICS IN MOVEMENT” was created, which aims to present students with a current tool linked to the gamification feature, in order to arouse a greater interest in interacting with the discipline. The board game “PHYSICS IN MOVEMENT”, has some curiosity and interaction resources applied to the kinematics content, as well as some rewards, in order to make the student feel challenged, being part of a fun and interactive game, ending for achieving a higher learning performance in the teaching of Physics.